Non-Darcy Forchheimer flow of ferromagnetic second grade fluid - T. Hayat; Salman Ahmad; M. Ijaz Khan; A. Alsaedi (Results in Physics, 2017)
This article discusses impacts of thermal radiation, viscous dissipation and magnetic dipole in flow of second grade fluid saturating porous medium. Porous medium is characterized by nonlinear Darcy-Forchheimer relation. Relevant nonlinear ordinary differential systems after using appropriate transformations are solved numerically. Shooting technique is implemented for the numerical treatment. Temperature, velocity, skin fraction and Nusselt number are analyzed. Keywords: Second grade fluid, Thermal radiation, Magnetic dipole, Viscous dissipation, Non-Darcy Forchheimer medium